The effect of starch isolation method on physical and functional properties of Portuguese nut starches. II. Q. rotundifolia Lam. and Q. suber Lam. acorns starches - Correia, Paula Reis; Nunes, Maria Cristiana; Beirão-da-Costa, Maria Luísa (Food Hydrocolloids, 2013)
A new starch was isolated from fruits of two acorn species, Quercus rotundifolia and Quercus suber by alkaline (A3S) and enzymatic (ENZ) methods and physical and functional properties were studied. The isolation method induced changes in most of those properties in the isolated starches, mainly in resistant starch content, syneresis, pasting, thermal and rheological properties. Isolated acorn starches presented high amylose content (53e59%) and resistant starch content (30.8e41.4%). Acorn starches showed limited and similar solubility values and swelling power values, showing a gradual increase from 60 C to 90 C. The pasting temperatures ranged from 67.5 to 72.0 C and pastes did not present breakdown, which is suggestive of a high paste stability of acorn starches during heating. At ambient temperature the turbidity and syneresis values were low, but when held at freezing temperatures the syneresis signiﬁ- cantly increased. Thermal analysis revealed that the acorn starches easily undergo transition phenomena as shown by the low To and enthalpy values (4.1e4.3 J/g), these effects were more evident in starches isolated by ENZ method. Pastes are more elastic than viscous and form strong gels after cooling. Q. suber starch was shown to be more sensitive to the effect of isolation method. Generally, starch isolated by enzymatic method presented less interesting functional properties, since this isolation procedure greater affected the raw structure of starches
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorns; Functional properties; isolation method; rheological properties; starch; thermal properties

Effect of Drying Temperatures on Starch-Related Functional and Thermal Properties of Acorn Flours - Correia, P R; Beirão-da-Costa, M L (Journal of Food Science, 2011)
Abstract: The application of starchy flours from different origins in food systems depends greatly on information about the chemical and functional properties of such food materials. Acorns are important forestry resources in the central and southern regions of Portugal. To preserve these fruits and to optimize their use, techniques like drying are needed. The effects of different drying temperatures on starch-related functional properties of acorn flours obtained from dried fruits of Quercus rotundifolia (QR) and Quercus suber (QS) were evaluated. Flours were characterized for amylose and resistant starch (RS) contents, swelling ability, and gelatinization properties. Drying temperature mainly affected amylose content and viscoamylographic properties. Amylograms of flours from fruits dried at 60 °C displayed higher consistency (2102 B.U. and 1560 B.U., respectively, for QR and QS). The transition temperatures and enthalpy were less affected by drying temperature, suggesting few modifications in starch structure during drying. QR flours presented different functional properties to those obtained from QS acorn flours. The effect of drying temperatures were more evident in QR.
Keywords: acorn flours; drying; Functional properties; starch; thermal analysis